UMPSA Gemilang. Cipta. Cinta. Citra. Sejarah Tercipta - Nurhidayah, Md Yunus (UMPSA, 2024)
The song still easily plays in my head even after years I graduated. It has been a journey. A great one, I would say. I remember the first time I set foot on campus: I felt excited, nervous, and eager to start my campus life.